2015
DOI: 10.1159/000375296
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pivotal Markers in Vascular Dementia Based on Proteomics Data

Abstract: Objective: The aim of this study was to analyze protein expression profiles of vascular dementia (VaD) subjects for investigating the underlying therapeutic markers. Methods: Protein expression profile data were acquired from a quantitative clinical proteomic study, including 10 nondemented elderly controls and 10 age-matched VaD subjects. Differentially expressed proteins (DEPs) were identified between VaD subjects and controls, followed by function prediction using DAVID (Database for Annotation, Visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…Therefore, despite the absence of clinical evidence for hippocampal hypometabolism in VaD patients, increased Na levels in VaD post-mortem tissue may imply hippocampal energy dysfunction in late-stage VaD. This observation is consistent with proteomic findings from the middle-temporal gyrus in VaD post-mortem tissue, whereby downregulation of ATP synthase (electron transport chain complex V; EC 7.1.2.2) subunits (Datta et al, 2014;Wang et al, 2015) and upregulation of Na/K-ATPase alpha subunit 3 (ATP1A3) (Adav et al, 2014) were identified. Elevated Na levels may also highlight the potential application of clinical 23 Na magnetic resonance imaging as a diagnostic method in VaD, which has already been shown to be informative in patients with multiple sclerosis (Inglese et al, 2010;Eisele et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, despite the absence of clinical evidence for hippocampal hypometabolism in VaD patients, increased Na levels in VaD post-mortem tissue may imply hippocampal energy dysfunction in late-stage VaD. This observation is consistent with proteomic findings from the middle-temporal gyrus in VaD post-mortem tissue, whereby downregulation of ATP synthase (electron transport chain complex V; EC 7.1.2.2) subunits (Datta et al, 2014;Wang et al, 2015) and upregulation of Na/K-ATPase alpha subunit 3 (ATP1A3) (Adav et al, 2014) were identified. Elevated Na levels may also highlight the potential application of clinical 23 Na magnetic resonance imaging as a diagnostic method in VaD, which has already been shown to be informative in patients with multiple sclerosis (Inglese et al, 2010;Eisele et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…This gives reason to believe that defective energy utilization leading to diminished pools of ATP could lead to the observed intracellular Na elevations seen here that are likely due to reduced Na + /K + -ATPase activity. This is further supported by proteomic evidence showing downregulation of ATP synthase (electron transport chain complex V; EC 7.1.2.2) subunits ( Datta et al, 2014 ; Wang et al, 2015 ) and upregulation of Na/K-ATPase alpha subunit 3 ( Adav et al, 2014 ) in VaD middle-temporal gyrus post-mortem tissue. Reduced activity of Na/K-ATPase can also lead to neuronal cell death ( Xiao et al, 2002 ; Kurauchi et al, 2018 ) potentially via glutamate neurotoxicity and alterations in dopamine release ( Lees, 1991 ), which could further exacerbate cerebrovascular pathology in VaD.…”
Section: Discussionmentioning
confidence: 60%
“…Two metabolic pathways, pentose and glucuronate interconversions ( Zheng et al, 2019 ), and starch and sucrose metabolism ( Ling et al, 2021 ) may play roles in learning and cognitive impairment that are caused by abnormal nitric oxide production and monoaminergic neurotransmitters in AD, BPD, and/or dementia patients. Other metabolisms, including porphyrin and chlorophyll metabolism ( Wang et al, 2015 ), and ascorbate and aldarate metabolism ( Chen et al, 2011 ) were biologically or molecularly connected with psychiatric disorders (e.g., AD, BPD) and dementia. We noticed that some of enriched network pathways that were not reported previously suggest that there may be potential links between BPD and the risk of dementia or possibly a chance association.…”
Section: Discussionmentioning
confidence: 99%